A study on factors influencing perception of users toward internet recruitment on JobsMalaysia portal / Nik Noraisyah Nik Abd Rahman - Nik Abd Rahman, Nik Noraisyah (Bachelor of Science (Hons) Statistics, 2015)
The purpose of this study was to identify the factor that most influencing the perception of users toward internet recruitment on JobsMalaysia portal between the three variables selected which are web usability, information provision and user friendliness. This study involved 100 samples from a list of participants that already listed in ‘e-Kasih’ system as the respondents by using simple random sampling. Data were collected by using the self-administered questionnaires that design by the researcher from the previous study. Multiple Regression method was used to identify the relevant relationship between the variables. The results of the study shows the variables that are significant are information provision and user friendliness meanwhile the variable that is not significant is web usability variable thus it can be concluded that the factors that influencing the perception of users towards internet recruitment are information provision and user friendliness. Furthermore, the result also shows that there is no association between gender and usage history on JobsMalaysia portal